Piezoelectric laminate and piezoelectric element

By using the first layer with high melting point metals such as W, Mo, Nb and Ta as the main components in the lower electrode layer of the electrode element, and forming an Ir layer of 50 nm or less as the second layer, the problem of dielectric phase growth is solved, and efficient dielectric constant maintenance and long-term reliability are achieved.

JP7667051B2Active Publication Date: 2025-04-22FUJIFILM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021157101
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-04-22
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

When using electrode elements containing electrode layers of skidite oxides, dielectric phases are easily formed, which can cause a decrease in dielectric constant and dielectric constant, which in turn affects the long-term reliability of the electrode elements.

Method used

A first layer with high melting point metals such as W, Mo, Nb and Ta as the main components, and an Ir layer of 50 nm or less is formed thereon as the second layer. By the lower electrode layer of this two-layer structure, the growth of the dielectric phase is reduced and the long-term reliability of the electrode element is improved.

Benefits of technology

It effectively suppresses the growth of the dielectric phase, maintains high dielectric and dielectric constants, improves the long-term reliability of the electrode components, and reduces material costs and manufacturing pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667051000002
    Figure 0007667051000002
  • Figure 0007667051000003
    Figure 0007667051000003
  • Figure 0007667051000004
    Figure 0007667051000004
Patent Text Reader

Abstract

To provide a piezoelectric laminate and a piezoelectric element capable of improving long-term reliability without reducing piezoelectric characteristics compared with the conventional art.SOLUTION: A piezoelectric laminate and a piezoelectric element comprise on a substrate a lower electrode layer and a piezoelectric film containing perovskite type oxide in this order. The lower electrode layer includes: a second layer arranged in contact with the piezoelectric film; and a first layer arranged at the substrate side from the second layer. The first layer contains one or more kinds of W, Mo, Nb, and Ta as a main component. The second layer contains Ir as a main component, having a thickness of 50 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]

[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being deployed in a variety of devices, including memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.

[0003] When applying piezoelectric elements to devices, it is desirable for the piezoelectric elements to have high piezoelectric properties because higher piezoelectric properties lead to lower power consumption. To date, methods have been investigated to improve the piezoelectric properties, such as improving the crystallinity of the piezoelectric film and reducing the resistance of the electrode layer.

[0004] As the lower electrode layer of a piezoelectric element, an Ir layer is often used from the viewpoints of adhesion to the piezoelectric film and low resistance. In order to reduce resistance, the Ir layer is generally made to have a thickness of 150 nm or more. Although the Ir layer has good adhesion to the piezoelectric film, it does not have good adhesion to the silicon substrate, so an adhesion layer made of a TiW layer or a Ti layer is often provided between the Ir layer and the substrate (Patent Documents 1 and 2).

[0005] Patent Document 3 proposes a laminated structure in which an Ir layer and an Au layer are laminated in order to further reduce the resistance of the lower electrode layer. By using Au, which has a higher conductivity than Ir, it is possible to achieve low resistance in the entire lower electrode layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 051644 [Patent Document 2] JP 2009-82052 A [Patent Document 3] JP 2010-056426 A Summary of the Invention [Problem to be solved by the invention]

[0007] When a piezoelectric film mainly composed of perovskite oxide is formed on an Ir layer, there is a problem that a pyrochlore phase, which is a different phase, is easily formed at the interface with the lower electrode layer. Since the pyrochlore phase is a paraelectric, its formation leads to deterioration of piezoelectric properties such as a decrease in dielectric constant and a decrease in piezoelectric constant. Furthermore, piezoelectric elements that contain the pyrochlore phase at the interface between the piezoelectric film and the lower electrode layer are more susceptible to peeling and have lower long-term reliability than piezoelectric elements in which the pyrochlore phase is suppressed.

[0008] As in Patent Document 3, low resistance can be achieved by providing an Au layer on the lower electrode layer. On the other hand, it has been found that when the lower electrode layer has an Au layer, the long-term reliability is lower than in the case of the laminated structure of an Ir layer and a TiW or Ti adhesion layer disclosed in Patent Documents 1 and 2. This is thought to be due to the diffusion of Au caused by the high temperature of film formation when sputtering the piezoelectric film on the lower electrode layer. It is speculated that Au has a relatively low melting point and diffuses into the piezoelectric film during film formation, making it more likely to cause leaks.

[0009] The technology disclosed herein has been made in consideration of the above circumstances, and aims to provide a piezoelectric laminate and a piezoelectric element that have improved long-term reliability without deteriorating the piezoelectric characteristics compared to conventional techniques. [Means for solving the problem]

[0010] Specific means for solving the above problems include the following aspects.

[0011] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, the lower electrode layer includes a second layer disposed in contact with the piezoelectric film and a first layer disposed closer to the substrate than the second layer; The first layer contains one or more of W, Mo, Nb, and Ta as a main component, The second layer contains Ir as a main component, and has a thickness of 50 nm or less.

[0012] In the piezoelectric laminate of the present disclosure, the second layer preferably has a thickness of 45 nm or less.

[0013] In the piezoelectric laminate of the present disclosure, it is preferable to provide a first adhesion layer between the substrate and the first layer, which improves adhesion between the substrate and the first layer.

[0014] The first adhesion layer is preferably a TiW layer.

[0015] In the piezoelectric laminate of the present disclosure, it is preferable to provide a second adhesion layer between the first layer and the second layer, which improves adhesion between the first layer and the second layer.

[0016] The second adhesion layer is preferably a TiW layer.

[0017] In the piezoelectric laminate of the present disclosure, the first layer is preferably a W layer.

[0018] In the piezoelectric laminate of the present disclosure, the perovskite oxide is a compound represented by the following general formula (1): Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) 0 <x<1、0<y<0.4、 B1 is preferably one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W.

[0019] In the piezoelectric laminate of the present disclosure, the half-width at half maximum of the X-ray diffraction peak from the (111) plane of Ir in the second layer is preferably 0.3° or more.

[0020] In the piezoelectric laminate of the present disclosure, the second layer is preferably a uniaxially oriented film in which Ir is oriented in the (111) plane, and the (111) plane is inclined at 1° or more with respect to the thickness direction.

[0021] In the piezoelectric laminate of the present disclosure, it is preferable that a pyrochlore phase is contained at the interface between the lower electrode layer and the piezoelectric film, and that the thickness of the pyrochlore phase is 20 nm or less.

[0022] The piezoelectric element of the present disclosure comprises: and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. Effect of the Invention

[0023] According to the piezoelectric laminate and piezoelectric element of the present disclosure, it is possible to improve the long-term reliability without deteriorating the piezoelectric characteristics as compared to the conventional art. [Brief description of the drawings]

[0024] [Figure 1] 1 is a cross-sectional view showing a layer structure of a piezoelectric element according to an embodiment of the present invention. [Diagram 2] 4 is an explanatory diagram of the orientation state of the second layer (Ir layer) of the lower electrode layer in the present embodiment. FIG. [Diagram 3] 1 is an explanatory diagram of the orientation of an Ir layer used as a lower electrode layer in a conventional piezoelectric element. [Figure 4] FIG. 2 is an enlarged schematic view of a piezoelectric film. [Diagram 5] 10 is a cross-sectional view showing a layer structure of a piezoelectric element according to Modification 1. FIG. [Figure 6] 11 is a cross-sectional view showing a layer structure of a piezoelectric element according to Modification 2. FIG. [Figure 7]FIG. 2 is a diagram showing the Ir(111) peak in the XRD chart of Example 1. [Figure 8] FIG. 1 shows the rocking curve of the Ir(111) peak for Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the thicknesses and ratios of each layer are appropriately changed for ease of viewing, and do not necessarily reflect the actual thicknesses and ratios.

[0026] "Piezoelectric laminate 5 and piezoelectric element 1 according to the first embodiment" Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 of the first embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, and a lower electrode layer 12 and a piezoelectric film 15 including a perovskite oxide, which are stacked on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12 and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.

[0027] In the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the lower electrode layer 12 includes a second layer 22 arranged in contact with the piezoelectric film 15, and a first layer 21 arranged on the substrate 10 side of the second layer 22. The first layer 21 includes one or more of W (tungsten), Mo (molybdenum), Nb (niobium), and Ta (tantalum) as a main component. Here, the term "main component" refers to a component that accounts for 95 wt% or more of the constituent elements. "Having one or more main components" means that only one of W, Mo, Nb, and Ta may be included as a main component, or two or more may be included as a combination of main components. When the first layer 21 includes only one of W, Mo, Nb, and Ta, that one component accounts for 95 wt% or more. For example, when the first layer 21 includes only W from the above group, it means that W accounts for 95 wt% or more. Also, when the first layer 21 contains two or more of W, Mo, Nb, and Ta, it means that the total of the two or more elements contained therein is 95 wt% or more. For example, when the first layer 21 contains W and Mo as main components, it means that the total of the W content and the Mo content is 95 wt% or more. It is particularly preferable that the first layer 21 is a layer containing W as the main component. W, Mo, Nb, and Ta are all high-melting point metals. Here, the high-melting point metal refers to a metal having a melting point of 1538°C or higher, which is the melting point of Fe (iron).

[0028] The second layer 22 is a layer containing Ir as a main component, and may be referred to as the Ir layer 22 below. The thickness t2 of the Ir layer 22 is 50 nm or less. The thickness t2 is preferably less than 50 nm, and more preferably less than 45 nm. The thickness t2 is preferably 10 nm or more. The inventors have found that by making the thickness t2 of the Ir layer 22 50 nm or less, preferably less than 50 nm, it is possible to suppress the growth of the pyrochlore phase in the initial stage of the deposition of the piezoelectric film 15 to be deposited on the Ir layer 22 (see Examples). The inventors speculate that by making the thickness t2 of the Ir layer 22 50 nm or less, the preferred orientation of the Ir (111) plane is not sufficiently oriented, and the crystallinity can be made low, and therefore it is possible to suppress the growth of the pyrochlore phase during the deposition of the piezoelectric film 15. It is preferable that the thickness of the Ir layer 22 is 10 nm or more, since the Ir layer 22 can be formed into a uniform film.

[0029] The first layer 21 is provided to ensure that the Ir layer 22 has sufficient conductivity as the lower electrode layer 12 since the Ir layer 22 has a thickness of 50 nm or less, which is thinner than conventional layers.

[0030] The overall thickness t of the lower electrode layer 12 is preferably 150 nm or more, more preferably 160 nm or more, and more preferably 170 nm or more.

[0031] The thickness t of the lower electrode layer 12 and the thickness t2 of the Ir layer 22 can be estimated from a scanning electron microscope (SEM) image, a transmission electron microscope (TEM) image, or a secondary ion mass spectrometry (SIMS) analysis of the cross section of the piezoelectric element.

[0032] The half-width at half maximum of the X-ray diffraction peak from the (111) plane in the Ir layer 22 (hereinafter referred to as the Ir(111) peak) is preferably 0.3° or more. The half-width at half maximum of the Ir(111) peak is more preferably 0.35° or more. The half-width at half maximum of the Ir(111) peak is preferably 0.45° or less, more preferably 0.4° or less.

[0033] Here, the half-width at half maximum of the Ir(111) peak is measured as follows. The upper electrode layer 18 of the piezoelectric element is removed, and an XRD chart is obtained by thin-film XRD (X-ray diffraction) diffraction in a state in which the lower electrode layer 12 and the piezoelectric film 15 are provided on the substrate 10. A prescribed function is fitted to the Ir(111) peak in the XRD chart. The Ir(111) peak appears near 2θ=40.7°. The half-width at half maximum is calculated as the distance between the 2θ value showing the maximum value of the peak shown by the fitting curve and the 2θ value that is half the maximum value and does not overlap with other peaks (see FIG. 7).

[0034] When Ir is deposited on a substrate by sputtering, a naturally oriented film is formed with preferential orientation in the (111) plane. Crystallinity is related to the half-width at half maximum of the Ir(111) peak in the XRD chart (see Figure X) obtained by XRD diffraction. The wider the half-width at half maximum of Ir(111), the lower the crystallinity, and the narrower the half-width at half maximum, the higher the crystallinity. A half-width at half maximum of 0.3° or more means that there is a disturbance in the orientation of the (111) plane of the Ir layer 22, and the crystallinity is somewhat low.

[0035] In this embodiment, the (111) plane of the Ir layer 22 is inclined at 1° or more with respect to the thickness direction.

[0036] FIG. 2 is a schematic diagram of the Ir layer 22 of this embodiment, and the particles 22a in the diagram represent Ir elements. As shown in FIG. 2, the inclination of the (111) plane to the thickness direction of 1° or more means that the inclination α of the direction perpendicular to the (111) plane

[0111] to the thickness direction N is 1° or more. Here, the thickness direction N is the thickness direction of the Ir layer, and is a direction perpendicular to the surface 10a of the substrate 10. The actual Ir layer 22 contains many crystals, and the inclination direction of the (111) plane of each crystal varies. In this specification, the inclination α of the (111) plane in the Ir layer 22 is defined as a value measured by rocking curve measurement by X-ray diffraction. Specifically, the inclination α of the (111) plane is calculated from the split width of the (111) diffraction peak in the rocking curve measurement data (see Examples).

[0037] The (111) plane is the preferred orientation plane of Ir, and conventionally, an Ir layer oriented so that the (111) plane is perpendicular to the thickness direction, i.e., the

[0111] direction coincides with the thickness direction N, as shown in Fig. 3, has been used as the lower electrode layer. When a piezoelectric film made of a perovskite oxide is formed on a highly crystalline Ir layer as shown in Fig. 3, a pyrochlore phase is likely to form in the early stages of film formation. In response to this, the present inventors have found that the growth of the pyrochlore phase can be suppressed by reducing the crystallinity of the Ir layer 22 (see Examples).

[0038] The Ir(111) plane preferably has an inclination α of 1° or more and 15° or less with respect to the thickness direction N, and more preferably has an inclination of 1° or more and 8° or less.

[0039] In addition, the greater the inclination α of the (111) plane in the first layer 21 with respect to the thickness direction N, the greater the effect of suppressing the growth of the pyrochlore phase, and this is preferable. On the other hand, by setting the inclination to 15° or less, it is possible to suppress the dominance of other oriented planes, which is also preferable.

[0040] The sheet resistance of the lower electrode layer 12 is preferably 1 Ω / □ or less, and more preferably 0.8 Ω / □ or less. The sheet resistance can be measured by a four-probe method using a resistivity meter.

[0041] The piezoelectric film 15 contains a perovskite oxide represented by the general formula ABO3. In the general formula, A is an A-site element and is one or a combination of two or more of Pb, Ba (barium), La (lanthanum), Sr, Bi (bismuth), Li (lithium), Na (sodium), Ca (calcium), Cd (cadmium), Mg (magnesium), and K (potassium). In the general formula, B is a B-site element, and is one or a combination of two or more of Ti, Zr, V (vanadium), Nb (niobium), Ta (tantalum), Cr (chromium), Mo (molybdenum), W (tungsten), Mn (manganese), Fe (iron), Ru, Co (cobalt), Ir, Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), In, tin, antimony (Sb), and lanthanide elements. In the general formula, O is oxygen. The standard ratio of A:B:O is 1:1:3, but it may deviate within the range in which a perovskite structure can be obtained.

[0042] Preferably, the perovskite oxide accounts for 80 mol % or more, and more preferably, 90 mol % or more of the piezoelectric film 15. Furthermore, the piezoelectric film 15 is preferably made of a perovskite oxide (however, containing inevitable impurities).

[0043] The perovskite oxide is preferably a lead zirconate titanate (PZT) type oxide containing Pb (lead), Zr (zirconium), Ti (titanium) and O (oxygen).

[0044] In particular, the perovskite oxide is preferably a compound represented by the following general formula (1) which contains an additive B in the B site of PZT. Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) Here, B1 is preferably at least one element selected from V (vanadium), Nb (niobium), Ta (tantalum), Sb (antimony), Mo (molybdenum), and W (tungsten). Most preferably, B1 is Nb. Here, 0 < x < 1 and 0 < y < 0.4. In the general formula (1), Pb:{(Zr x Ti 1+x ) 1-y B y}:O is based on 1:1:3, but may deviate within the range where a perovskite structure can be obtained.

[0045] B1 may be a single element such as only V or only Nb, or a combination of two or more elements such as a mixture of V and Nb, or a mixture of V, Nb, and Ta. When B1 is these elements, a very high piezoelectric constant can be realized in combination with Pb as the A-site element.

[0046] Note that the piezoelectric film 15 preferably has a columnar structure film including a large number of columnar crystals 17 as shown in the cross-sectional schematic diagram of FIG. 4. The large number of columnar crystals 17 preferably extend non-parallel to the surface of the substrate 10 (see FIG. 1) and are a uniaxially oriented film with aligned crystal orientations. By adopting an oriented structure, greater piezoelectricity can be obtained. The piezoelectric film 15 contains a pyrochlore phase 16 at the interface with the second layer 22 of the lower electrode layer 12. Although details will be described later, the pyrochlore phase 16 is in a state where it is sufficiently suppressed. The pyrochlore phase 16 is preferably 20 nm or less. Note that the pyrochlore phase 16 is not uniformly formed on the surface of the lower electrode layer 12, but grows partially as shown in FIG. 4. The method for calculating the thickness of the pyrochlore phase 16 will be described in the examples.

[0047] In the example shown in FIG. 4, the longitudinal direction of the columnar crystal has an inclination β of 1° or more with respect to the normal (thickness direction N) of the substrate. This means that the orientation plane of the piezoelectric film 15 has an inclination of 1° or more with respect to the surface of the substrate. Here, the orientation plane is the (100) plane or the (001) plane. Thus, in the piezoelectric film 15, it is preferable that the (100) plane or the (001) plane of the columnar crystal is inclined by 1° or more with respect to the surface of the substrate. In this example, the lattice constants of the a-axis and the c-axis in the perovskite structure are almost the same, and the (100) plane and the (001) plane cannot be distinguished by XRD analysis. However, it can be confirmed by XRD analysis that the film is oriented in at least one of the planes.

[0048] The thickness of the piezoelectric film 15 is usually 200 nm or more, for example, 0.2 μm to 5 μm, and preferably 1 μm or more.

[0049] The substrate 10 is not particularly limited, and examples thereof include substrates of silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, silicon carbide, etc. The substrate 10 may be a laminated substrate such as a silicon substrate with a thermally oxidized film, in which a SiO2 oxide film is formed on the surface of a silicon substrate.

[0050] The upper electrode layer 18 is an electrode that is paired with the lower electrode layer 12 and is used to apply a voltage to the piezoelectric film 15. There are no particular limitations on the main component of the upper electrode layer 18, and examples of the main component include electrode materials that are generally used in semiconductor processes, as well as conductive oxides such as ITO (Indium Tin Oxide), LaNiO3, and SRO (SrRuO3), and combinations of these.

[0051] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.

[0052] As described above, in the piezoelectric laminate 5 and the piezoelectric element 1 of the present disclosure, the lower electrode layer 12 includes the second layer 22 arranged in contact with the piezoelectric film 15, and the first layer 21 arranged on the substrate 10 side of the second layer 22. The first layer 21 contains at least one of W, Mo, Nb, and Ta as a main component, and the second layer 22 contains Ir as a main component, and the thickness of the second layer 22 is 50 nm or less. As described above, the Ir layer formed on the substrate by sputtering deposition is preferentially oriented in the (111) plane. The orientation of this (111) plane becomes higher as the thickness of the Ir layer 22 becomes thicker. Conventionally, in order to reduce the resistance of the lower electrode layer, the Ir layer is generally made to have a thickness of about 150 nm or more, and the crystallinity of the Ir layer when deposited to 150 nm is very high. The present inventors have found that when a piezoelectric film of a perovskite oxide is formed on an Ir layer, if the crystallinity of the Ir layer is too high, the pyrochlore phase is likely to grow, and that the growth of the pyrochlore phase can be suppressed by lowering the crystallinity of the Ir layer compared to conventional methods. If the thickness of the second layer 22, which is a layer mainly composed of Ir (Ir layer 22), is 50 nm or less, the crystallinity is not yet sufficiently high. Therefore, by forming a piezoelectric film 15 mainly composed of a perovskite oxide on the second layer 22 having a thickness of 50 nm or less, the growth of the pyrochlore phase can be suppressed. Since the pyrochlore phase can be suppressed, the piezoelectric characteristics can be improved and long-term reliability can be improved. In addition, by making the thickness of the Ir layer 22 50 nm or less, the amount of Ir used can be reduced compared to conventional methods, so that the material cost of the lower electrode layer 12 can be suppressed and the manufacturing cost can be suppressed.

[0053] Conventionally, the resistance of the lower electrode layer has been reduced by making the Ir layer approximately 150 nm or more, but it has been found that the large stress of the Ir layer is a factor preventing the improvement of long-term reliability. In the piezoelectric laminate 5 and piezoelectric element 1 of the present disclosure, the second layer 22 (here, the Ir layer 22) of the lower electrode layer 12 is 50 nm or less, so the stress is smaller than when a conventional Ir layer of approximately 150 nm is provided. The first layer 21 compensates for the conductivity that is reduced by making the second layer 22 50 nm or less. W, Mo, Nb, and Ta can all realize a lower electrode layer having a resistivity equivalent to that of a single Ir layer. In addition, when these metals are formed by sputtering deposition, the stress is smaller than that of Ir. Therefore, the long-term reliability can be improved.

[0054] Furthermore, since the melting points of W, Mo, Nb, and Ta constituting the first layer 21 are all sufficiently higher than Au, diffusion is unlikely to occur even when the deposition temperature of the piezoelectric film 15 is set to a high temperature (e.g., 700°C), and deterioration in long-term reliability can be suppressed compared to when an Au layer is provided as in Patent Document 3.

[0055] In addition, by setting the thickness of the second layer 22 to 45 nm or less, the crystallinity of Ir(111) can be further reduced, which can further suppress the growth of the pyrochlore phase during the formation of the piezoelectric film 15, thereby further improving the piezoelectric characteristics and long-term reliability.

[0056] In the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the Ir layer 22, which is the second layer 22, is a uniaxially oriented film oriented in the Ir (111) plane, and the half-width at half maximum of the X-ray diffraction peak from the (111) plane of Ir is 0.3° or more. As described above, the half-width at half maximum of the X-ray diffraction peak is 0.3° or more, which means that the crystallinity of the Ir layer 22 is somewhat low and the Ir layer 22 is not sufficiently oriented to the (111) plane, which is the preferred orientation plane. If the Ir (111) plane is disturbed, the growth of the pyrochlore phase can be suppressed during the deposition of the piezoelectric film 15 containing a perovskite oxide provided on the upper layer. Since the pyrochlore phase can be sufficiently suppressed, the piezoelectric laminate 5 and the piezoelectric element 1 can be obtained that include a good piezoelectric film 15 containing a perovskite oxide. Since the piezoelectric film 15 includes a piezoelectric film in which the pyrochlore phase is suppressed, high piezoelectric characteristics can be obtained, and higher driving stability than before can be obtained.

[0057] Furthermore, if the half-width at half maximum of the X-ray diffraction peak from the Ir(111) plane of the Ir layer 22 is 0.35° or more, the effect of suppressing the growth of the pyrochlore phase can be further improved, and as a result, the piezoelectric characteristics and driving stability can be further improved.

[0058] Furthermore, if the half-width at half maximum of the X-ray diffraction peak from the Ir (111) plane is 0.45° or less, preferably 0.4° or less, the growth of the pyrochlore phase can be suppressed while maintaining the resistance value of the Ir layer 22 and its adhesion to the piezoelectric film 15 at levels equivalent to those of a highly crystalline Ir layer.

[0059] In the piezoelectric laminate 5 and piezoelectric element 1 of this embodiment, the Ir(111) plane of the second Ir layer 22 is inclined at 1° or more with respect to the thickness direction. This indicates that there is a disturbance in the orientation of the Ir(111) plane, and similarly to a half-width at half maximum of 0.3° or more, this indicates low crystallinity. The slightly reduced orientation of the Ir(111) plane also provides an effect of suppressing the pyrochlore phase.

[0060] The piezoelectric film 15 contains a perovskite oxide, and when the piezoelectric film 15 contains a perovskite oxide containing Pb, the Pb is easily removed, and the pyrochlore phase is easily formed in the early stage of film formation. Therefore, the effect of suppressing the pyrochlore phase is particularly high when the half width at half maximum of the X-ray diffraction peak from the Ir (111) plane is 0.3° or more. Among the perovskite oxides containing Pb, PZT-based perovskite oxides containing Pb, Zr, Ti, and O are particularly preferred because of their high piezoelectric properties. In particular, the perovskite oxide is a compound represented by the following general formula (1), Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) 0 <x<1、0<y<0.4、 If B1 is one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W, even higher piezoelectric properties can be obtained.

[0061] In the above embodiment, the lower electrode layer 12 has a two-layer structure of the first layer 21 and the second layer 22, but may also include other layers.

[0062] Modified examples of the piezoelectric laminate 5 and the piezoelectric element 1 are shown in Fig. 5 and Fig. 6. In Fig. 5 and Fig. 6, the same components as those shown in Fig. 1 are denoted by the same reference numerals, and detailed description thereof will be omitted.

[0063] 5, the lower electrode layer 12A includes a first adhesion layer 23 between the substrate 10 and the first layer 21, the first adhesion layer 23 improving adhesion between the substrate 10 and the first layer 21. The first adhesion layer 23 is preferably a TiW layer or a Ti layer, and is particularly preferably a TiW layer.

[0064] By providing the first adhesive layer 23 between the substrate 10 and the first layer 21, it is possible to suppress delamination and further improve long-term reliability.

[0065] 6, the lower electrode layer 12B includes a first adhesion layer 23, similar to the piezoelectric laminate 5A and piezoelectric element 1A of Modification 1, and further includes a second adhesion layer 24 between the first layer 21 and the second layer 22. The second adhesion layer 24 is provided to improve adhesion between the first layer 21 and the second layer 22. Like the first adhesion layer 23, the second adhesion layer 24 is preferably a TiW layer or a Ti layer, and is particularly preferably a TiW layer.

[0066] By providing the second adhesive layer 24 between the first layer 21 and the second layer 22, it is possible to suppress delamination and further improve long-term reliability. By providing the first adhesive layer 23 and the second adhesive layer 24, it is possible to further improve long-term reliability compared to the case where only one of them is provided.

[0067] Furthermore, as yet another modified example of the piezoelectric laminate and piezoelectric element, a configuration may be adopted in which the first adhesion layer 23 is not provided between the substrate 10 and the first layer 21, and only the second adhesion layer 24 is provided between the first layer 21 and the second layer 22.

[0068] It is particularly preferable that the first layer 21 of the lower electrode layer 12 is W and the first adhesion layer 23 (and the second adhesion layer 24) is TiW. In this case, TiW contains less than 95 wt% W. When the first layer 21 is W and the first adhesion layer 23 (and the second adhesion layer 24) is TiW, adhesion is particularly good and the effect of improving reliability is remarkable.

[0069] The piezoelectric element 1 or the piezoelectric laminate 5 in each of the above-described embodiments is applicable to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES

[0070] Specific examples and comparative examples of the piezoelectric element of the present disclosure will be described below. First, a method for producing the piezoelectric element of each example will be described. A radio frequency (RF) sputtering device was used to deposit each layer. Conditions other than the configuration of the lower electrode layer were the same for each example. The manufacturing method will be described with reference to the reference numerals of each layer of the piezoelectric element 1B shown in FIG. 6.

[0071] (Bottom electrode layer deposition) An 8-inch silicon substrate with a thermal oxide film was used as the substrate 10. The lower electrode layer 12 was formed on the thermal oxide film, which was the surface of the substrate 10. The layer configuration of the lower electrode layer 12 in each example was as shown in Table 1. For example, in the case of Example 1, the lower electrode layer 12 was formed by forming a 20 nm TiW layer as the first adhesion layer 23, a 100 nm W layer as the first layer 21, a 20 nm TiW layer as the second adhesion layer 24, and further a 50 nm Ir layer as the second layer 22.

[0072] The sputtering conditions for each layer were as follows: The target-substrate distance was 100 mm and the substrate temperature was set to 350° C.

[0073] -TiW layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.5 Pa

[0074] -Ir layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.1 Pa

[0075] -Au layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.1 Pa

[0076] -W layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.1 Pa

[0077] -Mo layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.1 Pa

[0078] -Ta layer sputtering conditions- Target input power: 600W Ar gas pressure: 0.1 Pa

[0079] (Piezoelectric film deposition) The substrate 10 with the lower electrode layer 12 was placed in an RF sputtering device, and a Nb-doped PZT film with a B site doping amount of 12 at % was formed to a thickness of 2 μm as the piezoelectric film 15. The sputtering conditions at this time were as follows:

[0080] -Piezoelectric film sputtering conditions- Target-substrate distance: 60mm Target input power: 500W Ar / O2 gas pressure: 0.3 Pa, Ar / O2 mixed atmosphere (O2 volume fraction 2.0%) Substrate temperature setting: 700℃

[0081] (Top electrode layer formation) Next, the substrate 10 after the formation of the piezoelectric film 15 was placed in a deposition chamber of an RF sputtering device, and an ITO (Indium Tin Oxide) target was used to form an ITO layer having a thickness of 200 nm as the upper electrode layer 18. Before forming the upper electrode layer 18, a lift-off pattern for an evaluation sample was prepared on the piezoelectric film 15, and the upper electrode layer 18 was formed on the lift-off pattern. The deposition conditions for the upper electrode layer 18 were as follows:

[0082] -Upper electrode layer sputtering conditions- Target-substrate distance: 100mm Target input power: 200W Degree of vacuum: 0.3 Pa, Ar / O2 mixed gas (O2 volume fraction 5%) Substrate temperature setting: RT (room temperature) Substrate temperature: Room temperature

[0083] (Formation of electrode pattern for evaluation) After the upper electrode layer 18 was formed, the upper electrode layer was lifted off along a lift-off pattern by a lift-off method, and the upper electrode layer 18 was patterned.

[0084] By the above steps, a piezoelectric laminate substrate of each example was fabricated, which had a lower electrode layer, a piezoelectric film, and a patterned upper electrode layer on a substrate.

[0085] (Preparation of evaluation samples) -Evaluation sample 1- A rectangular piece measuring 2 mm×25 mm was cut out from the piezoelectric laminate substrate to prepare a cantilever as evaluation sample 1.

[0086] -Evaluation sample 2- A 25 mm×25 mm portion having an upper electrode layer patterned into a circle with a diameter of 400 μm at the center of the surface of the piezoelectric film was cut out from the piezoelectric laminate substrate, and used as evaluation sample 2.

[0087] <Evaluation of piezoelectric properties> The piezoelectric properties of each example and comparative example were evaluated using the piezoelectric constant d 31 was measured. Piezoelectric constant d 31 The measurement was performed by cutting the piezoelectric element prepared as above into a rectangular shape of 2 mm x 25 mm to prepare a cantilever, and following the method described in I. Kanno et. al. Sensor and Actuator A 107 (2003) 68., by grounding the lower electrode layer 12 and applying a sine wave voltage of -10 V ± 10 V to the upper electrode layer 18. The results are shown in Table 1.

[0088] <Long-term reliability evaluation> A time-dependent dielectric breakdown (TDDB) test was conducted to evaluate the long-term reliability of each of the examples and comparative examples. Using evaluation sample 2, the lower electrode layer 12 was grounded in an environment of 120° C., and a voltage of −40 V was applied to the upper electrode layer 18 to measure the time (hr) from the start of voltage application until dielectric breakdown occurred, and the long-term reliability was evaluated based on the time until dielectric breakdown occurred. The measurement results are shown in Table 1.

[0089] <Measurement of resistivity> Using a low-resistivity meter Loresta-AX, the resistivity (sheet resistance) of the lower electrode layer 12 was measured with a dedicated four-probe probe. For each example, the resistivity was measured when the lower electrode layer 12 was formed on the substrate 10.

[0090] <Half-width at half maximum of the Ir(111) peak> For each of the examples and comparative examples, the half-width at half maximum of the Ir(111) peak was determined by XRD analysis using a RIGAKU RINT-ULTIMAIII. From the XRD charts obtained for each example, the half-width at half maximum of the Ir(111) peak was determined. The Ir(111) peak occurs near 40.7°. Fig. 7 is an enlarged view of the vicinity of Ir(111) in the XRD chart of Example 1. Ir(111) occurs near 2θ = 40.7°. In Example 1 shown in Fig. 7, the peak of the TiW layer, which is the first layer of the lower electrode layer, partially overlaps with the Ir(111) peak. For such a peak, fitting was performed using a double Gaussian function. In the fitting curve of the Ir(111) peak, the width between the 2θ value indicating the maximum value Ip of the Ir(111) peak and the 2θ value indicating half the intensity of the maximum value Ip was taken as the half-width at half maximum (HWHM). The results are shown in Table 1.

[0091] <Inclination of the Ir(111) plane of the lower electrode layer from the substrate surface> For the examples and comparative examples, the crystallinity of the first layer was evaluated by XRD using RINT-ULTIMAIII manufactured by RIGAKU. Specifically, the tilt of the (111) plane was obtained by measuring the rocking curve and determining the deviation of the peak of the Ir (111) plane from the Ir peak position when the (111) plane is not tilted. FIG. 8 shows rocking curve measurement data for Example 1. The reference position shown in the figure is the peak position of the (111) plane that occurs when the (111) plane is parallel to the surface of the substrate. In the example shown in FIG. 8, there is a first peak P1 and a second peak P2, and the split width is 10°. The center of the split width of the first peak P1 and the second peak P2 is the reference position, which means that in this example, the (111) plane of the first layer is tilted by 5° with respect to the state parallel to the substrate. The measured values ​​for each example are shown in Table 1.

[0092] <Pyrochlore phase thickness evaluation> For the examples and comparative examples, TEM (Transmission Electron Microscope) images were taken, and the thickness of the pyrochlore phase was determined from the TEM images. In the piezoelectric film, the contrast in the TEM images is different between the pyrochlore phase and the perovskite phase, so the region of the pyrochlore phase can be identified and the thickness can be calculated. It was observed that columnar crystals of perovskite-type oxide were formed in the parts of the piezoelectric film other than the pyrochlore phase. The thickness of the pyrochlore phase was calculated as an average thickness because the pyrochlore phase was not uniformly formed on the surface of the lower electrode layer. Even if the pyrochlore phase is hardly visible on the XRD chart, the pyrochlore phase 16 is partially present as shown in the schematic diagram of FIG. 4, and this can be confirmed in the TEM image.

[0093] Specifically, the original image is binarized at a predetermined threshold value using the contrast adjustment function of the image processing software, and the pyrochlore phase is extracted using the edge extraction function of the image processing software. The threshold value in this case is set so that noise is removed as much as possible and only those that can be clearly identified as pyrochlore phase are extracted. If the outline of the pyrochlore-type oxide layer is unclear in the binarized image, a contour line is empirically drawn while looking at the binarized image and the inside is filled in. The area of ​​the extracted pyrochlore phase is calculated from the number of pixels of the image processing software and divided by the field width of the TEM image to obtain the average layer thickness. Photoshop (registered trademark) was used as the image processing software here. The thickness of the pyrochlore phase obtained as described above is shown in Table 1.

[0094] [Table 1]

[0095] As shown in Table 1, when the first layer of the lower electrode layer contains one or more of W, Mo, Nb, and Ta as a main component, the second layer contains Ir as a main component, and the thickness of the second layer is 50 nm or less, as in Examples 1 to 11, the piezoelectric constant is high and the long-term reliability is high. Comparative Example 1, in which the lower electrode layer does not include a layer containing one or more of W, Mo, Nb, and Ta as a main component and the Ir layer is 150 nm, and Comparative Examples 3 and 4, in which the first layer of the lower electrode layer is Au and Ir, had low long-term reliability. In addition, Comparative Example 2, in which the lower electrode layer does not include a layer containing one or more of W, Mo, Nb, and Ta as a main component, even if the Ir layer was 50 nm, had a low piezoelectric constant and a high resistivity.

[0096] In addition, a comparison of Examples 1 to 4 showed that, among W, Mo, Nb, and Ta, Example 1, in which the first layer is made of W, has the best long-term reliability, and Examples 1 and 6 to 10 showed that it is preferable that the Ir layer, which is the second layer of the lower electrode layer, has a thickness of 50 nm to 20 nm, and that the piezoelectric constant is 200 pm / V or more and the long-term reliability test is 1000 hours or more. Furthermore, since the piezoelectric constant is 210 pm / V or more and the long-term reliability test is 1100 hours or more, it is more preferable that the Ir layer, which is the second layer of the lower electrode layer, has a thickness of 45 nm to 30 nm. [Explanation of symbols]

[0097] 1,1A,1B Piezoelectric element 5,5A,5B Piezoelectric laminate 10 Substrate 12 Lower electrode layer 15 Piezoelectric film 16 Pyrochlore phase 17 Columnar crystals 18 Upper electrode layer 21 1st layer 22 2nd layer (Ir layer) 22a Ir element 23 First adhesive layer 24 Second Adhesive Layer

Claims

1. A piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, the lower electrode layer includes a second layer disposed in contact with the piezoelectric film, and a first layer disposed closer to the substrate than the second layer; The first layer contains one or more of W, Mo, Nb, and Ta as a main component, the second layer is mainly composed of Ir and has a thickness of 50 nm or less; A piezoelectric laminate comprising a second adhesion layer disposed between the first layer and the second layer, the second adhesion layer improving adhesion between the first layer and the second layer.

2. The piezoelectric stack of claim 1 , wherein the second layer has a thickness of 45 nm or less.

3. 3. The piezoelectric laminate according to claim 1, further comprising a first adhesion layer between the substrate and the first layer, the first adhesion layer improving adhesion between the substrate and the first layer.

4. The piezoelectric stack according to claim 3 , wherein the first adhesion layer is a TiW layer.

5. The piezoelectric laminate according to claim 1 , wherein the second adhesive layer is a TiW layer.

6. The piezoelectric stack of claim 1 , wherein the first layer is a W layer.

7. The perovskite oxide is a compound represented by the following general formula (1): ________________ x () 1-x ))) y ッ 3 () 0<x<1, 0<y<0.4, 7. The piezoelectric laminate according to claim 1, wherein B1 is one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W.

8. 8. The piezoelectric stack according to claim 1, wherein the X-ray diffraction peak from a (111) plane of the Ir in the second layer has a half width at half maximum of 0.3° or more.

9. 9. The piezoelectric laminate according to claim 1, wherein the second layer is a uniaxially oriented film in which the Ir is oriented in a (111) plane, and the (111) plane has an inclination of 1° or more with respect to a thickness direction.

10. a pyrochlore phase is included at the interface between the lower electrode layer and the piezoelectric film, The piezoelectric laminate according to claim 1 , wherein the pyrochlore phase has a thickness of 20 nm or less.

11. The piezoelectric laminate according to any one of claims 1 to 10, and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.

Citation Information

Patent Citations

  • Structure of semiconductor memory

    JP2000036569A

  • Plasma cleaning method and method of manufacturing semiconductor device

    JP2002025991A

  • Semiconductor device and method for manufacturing the same

    JP2004153019A

  • Piezoelectric element, ink jet head, method of manufacturing them, and ink jet-type recording device

    JP2004186646A

  • Fishing rod

    JP2009082052A